The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/jsfa.4607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reforestation on nitrogen and phosphorus dynamics in the catchment ecosystems of subtropical China: the example of the Hanjiang River basin

Abstract: The results suggest that RFCL is an effective policy for watershed environment management, which might have a relatively small effect on river discharge but that the purification effects on water quality in the river would be remarkable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In a similar SWAT modelling study, Wang et al . () evaluated the effects of the RFCL initiative in the Hanjiang River basin, a large subtropical catchment in the Shaanxi and Hubei provinces. The simulation results showed that RFCL (scenario: cultivated lands with a slope >15° were reforested) would cause an obvious decrease in surface runoff (−23·6%) but an increase in groundwater flow (71·8%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar SWAT modelling study, Wang et al . () evaluated the effects of the RFCL initiative in the Hanjiang River basin, a large subtropical catchment in the Shaanxi and Hubei provinces. The simulation results showed that RFCL (scenario: cultivated lands with a slope >15° were reforested) would cause an obvious decrease in surface runoff (−23·6%) but an increase in groundwater flow (71·8%).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies (e.g. Wang et al ., ) only considered analyses at the subbasin level. But water flows are created at the HRU level, influenced by the different combinations of slope, soil and land use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SWAT has been used extensively to evaluate the effects of land use change on discharge and water quality (e.g. see Jha et al ., 2010a,b; Schilling et al ., ; Bharati and Jayakody, ; Babel et al ., ; Nie et al ., ; Palamuleni et al ., ; Wang et al ., ). Schilling et al .…”
Section: Introductionmentioning
confidence: 97%
“…It plays an essential role in maintaining regional ecological and environmental functions, as well as sustaining agricultural production and socioeconomic development [3,[12][13][14]. Around 2000, many national construction projects related to afforestation and dams were carried out in this region, such as the construction of forest protection in the middle-lower Yangtze River starting in 2000, and the operation of the Three Gorges Dam starting in 2003, which significantly influenced the adjacent ecological environment [15][16][17]. As a result of the increase in anthropogenic activities over the past decades, most of the large lakes and reservoirs are now mesotrophic and even eutrophic in the MLYR basin, including Poyang Lake, Dongting Lake, Taihu Lake, and Chaohu Lake, which are the first-, second-, third-and fifth-largest freshwater lakes in China, respectively [18].…”
Section: Introductionmentioning
confidence: 99%